ANALISIS PENGARUH ANGIN TERHADAP POLA ARUS PERMUKAAN DAN DISTRIBUSI SALINITAS DI MUARA SUNGAI PALU - Jayadi, Harsano; Meidji, Icha Untari; Mudin, Yutdam; Botjing, Muslimin U (Universitas Islam Negeri Alauddin Makassar, 2020)
The pattern of surface currents and salinity distribution at the mouth of the Palu River by using the 2D coherens model to show that the presence of wind factors influences the velocity and direction of the tidal and non-tidal surface flow patterns at the mouth of the Palu River. Using primary and secondary data, the results show that non-tidal currents are more dominant with the direction of spread from the North to the East to the West then turn to the South, with a velocity of 2.57 m/s. The pattern of salinity distribution with tidal and non-tidal flow generators has a different model. Still, it has the same direction, namely the flow from North East to West direction, which is deflected to the South adjacent to the mouth of the Palu River estuary.Â